Evaluation of Pt, Rh, SnO2, (NH4)2Mo3S13, BaSO4 protection coatings on WSe2 photocathodes for solar hydrogen evolution. (31st July 2020) - Bozheyev, Farabi; Xi, Fanxing; Ahmet, Ibbi; Höhn, Christian; Ellmer, Klaus
Abstract: The stability of photoelectrodes is of prime importance, which determines the long-term efficiency of solar to hydrogen conversion. To this respect, the performances of Pt, Rh, SnO2, (NH4 )2 Mo3 S13 (ATM), BaSO4 are compared as protection coatings for WSe2 photocathodes. It is found that Pt and Rh catalysts, selectively photodeposited at the active edges of WSe2 crystallites, are not able to sustain the maximum photocurrent densities for hydrogen evolution reaction due to surface oxidation. By comparison, the ATM layer effectively passivates the van der Waals planes of WSe2, however, it is oxidized with further amorphization, thus decreasing the photocurrent density by 82% after 3 h 10 min of PEC testing. The SnO2 layer on top of ATM/WSe2 stabilizes the photocurrent to some extent, but limits the maximum photocurrent density. Solution deposition of BaSO4 onto ATM/WSe2 photocathodes did not compromise the photocurrent density and resulted in significant improvement of the PEC stability. Herein, the photocurrent density is decreased by 44% after 3 h 10 min of testing, which is rather less than that of bare ATM/WSe2 . The chemical states of all photocathodes are assessed by XPS analysis, before and after PEC testing, which identified that the BaSO4 suppresses photo-corrosion of the ATM. Graphical abstract: Image 1 Highlights: Pt and Rh catalysts at edges of WSe2 crystals do not stabilize the photocurrent. ATM increases photocurrent from WSe2, however, it is oxidized after PEC testing. SnO2 stabilizes ATM/WSe2, but limits the maximum photocurrent. BaSO4 stabilizes ATM/WSe2 and does not inhibit photocurrent.